Analysis of Electronic Banking and Its Impact on the Excellence of Banks in Croatia (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
Internet, as a global communications network, forms electronic market and the supply of many new services which have a huge impact on business and society. IT has made enormous changes in the financial sector and today is an important factor for the successful achievement of banks targets. Bank information systems are the basis of each bank and without these extremely complex systems, today there would be neither internet banking, nor mobile and it is no surprise that the banks give special attention to precisely these systems in order to be successful in the market where customers’ expectations rise as each day passes by.This paper has defined five approaches which lead to business excellence banks, which together form a system. It presents the research which will provide answers to various questions related to analysis of implementation and functionality of e-banking services in the Croatia. The purpose of this study was to observe the concept of business excellence and whose improvement leads to more performance. Considering that the banking is an important part of the economy and it is closely associated with the technology, conducted research will answer the variety of questions and user needs while visiting the banks Websites.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.